2018
DOI: 10.1016/j.ejmech.2017.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Development of potent and proteolytically stable human neuromedin U receptor agonists

Abstract: Neuromedin U (NMU) is a highly conserved endogenous peptide that is involved in a wide range of physiological processes such as regulation of feeding behavior, the stress response and nociception. The major limitation to use NMU as a therapeutic is its short half-life. Here, we describe the development of a set of novel NMU-analogs based on NMU-8, by introducing unnatural amino acids into the native sequence. This approach shows that it is possible to generate molecules with increased potency and improved plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…The stability of peptides can be measured in serum, plasma, or whole blood from humans or animals to assess the suitability of peptides as therapeutic drugs [ 7 , 9 15 ]. Many potential therapeutic peptides have shown to be partially or fully degraded in biological matrices, including antibacterial peptides [ 7 , 10 ], hormone peptides [ 9 , 15 ], neuropeptides [ 16 , 17 ], and anti-cancer peptides [ 18 ], which has ultimately limited their use as therapeutics. Enzyme degradation in the blood has led to the development of different strategies to improve peptide stability, including chemical modification, peptide self-assembly, the use of protease and peptidase inhibitors, or formulating the peptide in a drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of peptides can be measured in serum, plasma, or whole blood from humans or animals to assess the suitability of peptides as therapeutic drugs [ 7 , 9 15 ]. Many potential therapeutic peptides have shown to be partially or fully degraded in biological matrices, including antibacterial peptides [ 7 , 10 ], hormone peptides [ 9 , 15 ], neuropeptides [ 16 , 17 ], and anti-cancer peptides [ 18 ], which has ultimately limited their use as therapeutics. Enzyme degradation in the blood has led to the development of different strategies to improve peptide stability, including chemical modification, peptide self-assembly, the use of protease and peptidase inhibitors, or formulating the peptide in a drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme degradation in the blood has led to the development of different strategies to improve peptide stability, including chemical modification, peptide self-assembly, the use of protease and peptidase inhibitors, or formulating the peptide in a drug delivery system. Chemical modifications that can be used to prevent enzyme recognition and reduce degradation include altering the N- and C-terminals, cyclisation, polymerization, and the incorporation of non-natural amino acids [ 2 , 8 , 9 , 15 , 16 , 19 21 ]. However, modifications to the peptide structure carry the inherent risk that activity, receptor affinity, or receptor selectivity may be reduced or lost upon modification [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tritiated NMU-8, which was used for the binding studies, was obtained as described before (see Supporting Information for experimental details). 13 Evaluation of the affinities and agonistic activities of the NMU-analogs at the NMURs was performed in the present study on HEK293 cells transiently expressing human (h)NMUR1 and hNMUR2 as reported before. 13 Evaluation of the affinity of the novel NMU-analogs for the NMURs was performed with a competitive binding assay using [ 3 H]-NMU-8 as radioligand.…”
mentioning
confidence: 99%
“…13 Evaluation of the affinities and agonistic activities of the NMU-analogs at the NMURs was performed in the present study on HEK293 cells transiently expressing human (h)NMUR1 and hNMUR2 as reported before. 13 Evaluation of the affinity of the novel NMU-analogs for the NMURs was performed with a competitive binding assay using [ 3 H]-NMU-8 as radioligand. An inositol triphosphate (IP 3 ) accumulation assay was carried out to study the functional activity of the NMU-analogs.…”
mentioning
confidence: 99%
See 1 more Smart Citation